Monks and the Hierarchical Church in Egypt and the Levant During Late Antiquity : With a Chapter on Persian Christians in Late Antiquity by Adam Izdebski. - Wipszycka, E. (Journal of juristic papyrology. Supplement., 2021)
Many modern scholars of late antique Christianity are convinced that there was a structural conflict between the Church of the bishops and monasticism, which was a charismatic movement that emerged alongside the Church hierarchy understood as a (reasonably) stable institution ruled by largely non-charismatic laws.0The author has decided to verify the validity of this opinion. She has studied groups of sources which focus on particular events and people in order to trace the social and political context of the conflicts, and to determine to what extent they were rooted in doctrinal controversies rather than the charisma, or the lack thereof, of the protagonists of ecclesiastical history. The book is therefore a collection of case studies in relations between the Church and monasticism in the vast area from Egypt to the Sasanian Empire. The studies show the full extent of the diversity of the relations between monastic groups and clergy.